Community-Acquired Methicillin-Resistane Staphylococcus aureus: Getting over It - LE Nicolle (Canadian Journal of Infectious Diseases and Medical Microbiology)
There are three sure things in life: death, taxes and antimicrobial resistance appearing on the heels of the introduction and widespread use of an antimicrobial agent. Staphylococcus aureus has always been a poster child for the emergence of antimicrobial resistance (1). Penicillin-resistant strains of S aureus surfaced immediately following the introduction of penicillin in the late 1940s; within a few years, most hospital strains were penicillin resistant. There was also the rapid emergence of methicillin-resistant S aureus (MRSA) following the introduction of methicillin in the 1960s. While the replacement of nosocomial methicillin-susceptible S aureus by MRSA has proceeded at different rates in different regions, the overall global progression has been relentless. MRSA became common in Canadian health care facilities later than in the United States; however, since the early 1990s, nosocomial MRSA in Canada has steadily and irrevocably increased (2).